Pengaruh Fasilitas Belajar terhadap Hasil Belajar Kelas X-1 Mata Pelajaran Ekonomi SMA PGRI 2 Kota Bekasi - Lubis, Nurhasanah; Karyadi, Karyadi (FOCUS, 2023)
The research aims to determine the effect of Learning Facilities on the Learning Outcomes of class X students in the subject of Economics at SMA PGRI 2 Bekasi city. The research method used is associative quantitative method. The sampling technique uses a saturated sample with a sample size of 40 students at SMA PGRI 2 Bekasi City. The data used is simple linear regression analysis. Based on the research results of hypothesis testing calculations, it was obtained that tcount was -1.024 and ttable value was 2.024. This means that tcount < ttable, namely -1.024 <2.024, then H0 is accepted and Ha is rejected, meaning that the facilities do not have a significant effect on the learning outcomes of class X students in economics. then based on the results of the coefficient of determination test it can be seen that the coefficient of determination obtained is 0.027. It can be concluded that the contribution of Learning Facilities (x) to Learning Outcomes (Y) is 2.7% while the remaining 97.3% is influenced by other variables not explained in this study.